Psychiatric consultation requests by inpatient medical teams: an observational study - Carla Pezzia; Jacqueline A. Pugh; Holly J. Lanham; Luci K. Leykum (BMC, 2018)
Abstract Background We describe the way psychiatric issues are addressed by inpatient medical teams through analysis of discussions of patients with behavioral health concerns and examination of teams' subsequent consultation practices. Methods We observed morning rounds for nine inpatient medical teams for approximately month-long periods, for a total of 1941 observations. We compared discussions of patients admitted for behavioral health related medical conditions between those who did and did not receive a psychiatric consultation, developing categories to describe factors influencing consultation or other management. Results Out of 536 patients, 40 (7.5%) received a psychiatry consult. Evaluation of a known concern (i.e., substance use, affective disorder, or suicidal ideation) was the most common reason for referral (41.7%). Requests for medication review were second (30.6%). Thirty patients with concomitant behavioral and medical health issues did not receive a psychiatry consult. Cirrhosis with active substance use was the most common medical diagnosis (15), followed by alcohol withdrawal (9). Conclusions Four primary themes emerged from our data: positive identification of behavioral health issues by physicians, medication management as a primary reason for referral, patient preference in physician decision-making, and poor management of substance abuse. Our results identify two potential areas where skills-building for inpatient physicians could have a positive impact: management of medication and of substance abuse management.